Análise da construção do conhecimento nas equipes de alta performance: estudo de caso em uma concessionária de energia elétrica - Costa, Sávio Ricardo Muniz Aires da (2013)
Knowledge management in the corporate world has become a great opportunity for companies who observe this intangible resource (knowledge) a competitive advantage for sustainable success of the organization. The current business environment in a new way of operating, trying different scenarios before the existing evidence of the importance of knowledge in its various forms, to achieve these results. Thus, the process of knowledge creation is increasingly a premise in organizations as an aid in the formation and sustainability teams. This study aimed to analyze the construction of knowledge in a distributor of electricity in high performance teams.The methodology adopted in this case study was the use of document analysis, observation and interviews to validate the process of construction of knowledge according to authors Nonaka and Takeuchi, as well as the indirect measurement of knowledge using the Balanced Scorecard Kaplan and Norton. In addition, a questionnaire was applied with closed questions for measuring the maturity of the team, according to the model Dyer.In conclusion, this study showed that the organizational process of the teams is a facilitator in the knowledge conversion, where models of knowledge conversion would welcome the creation of organizational knowledge. In this context, the indirect measurement of knowledge using the BSC, revealed an evolution of performance indicators in the study area by 90 %, representing a significant contribution to the results obtained in the measurement of knowledge to evaluate the performance of the teams. In this respect, according to the model Dyer presented the results were significant and signaled teams mature and high performance. Thus, the present study allowed as in the construction of knowledge, from the SECI process, the routine of high performance teams in a power utility.